Pembuatan Nutrisi dan Penyuluhan Penyakit Hipertensi pada Anggota PKK Delima Jakarta Timur - Anggia, Vivi; Wiyati, Tuti; Wulandari, Nora (Uhamka Press, 2019)
According Data of SUDINKES of Jakarta in 2016 showed that the East Jakarta had a higher population of hypertension compared to other regions, which were as many as 98422 people. Consumption of fruits and vegetables every day provides many benefits for our body, not only it taste is good but fruit and vegetables are rich in antioxidants that are useful for preventing oxidative stress and can be an effort to prevent and treat hypertension. Various fruits and vegetables that have been studied provide antihypertensive properties. At this community service we held a training in making nutrition and counseling for hypertension in PKK members RT. 014 Perumnas Klender East Jakarta. The fruits and vegetables we use are starfruit, watermelon, lemon, celery and cucumber.